Thermosphere variation at different altitudes over the northern polar cap during magnetic storms. (August 2016) - Huang, Yanshi; Wu, Qian; Huang, Cheryl Y.; Su, Yi-Jiun
Abstract: In this study, we report observations and simulation results of heated neutrals at various altitudes inside the polar cap during two magnetic storms in January 2005. The Poynting flux measurements from the Defense Meteorological Satellite Program (DMSP) satellites show enhanced energy input in the polar cap during the storm main phase, which is underestimated in the TIE-GCM simulation. Neutral temperature measurements at 250 km from the ground-based Fabry-Perot Interferometer (FPI) at Resolute Bay are presented, along with the neutral density observations at 360 km and 470 km from Challenging Minisatellite Payload (CHAMP) and the Gravity Recovery and Climate Experiment (GRACE) satellites, respectively. These data have been analyzed to demonstrate the altitudinal dependence of neutral response to the storm energy input. By comparing the TIE-GCM simulation results and the observations, we demonstrate that Poynting fluxes as well as the thermosphere response were underestimated in the model. The simulated neutral temperature at Resolute Bay increases by approximately 260° and 280° K for the two events, respectively, much lower than the observed temperature enhancements of 750° and 900° K. Neutral density enhancements with more than 30% increase over the background density were also observed at polar latitudes, with no clear distinction between the auroral zone and polar cap. All measurements indicate enhancements at high latitudes poleward of 80° magnetic latitude (MLAT) implying that substantial heating can occur within the polar cap during storms. Highlights: Various neutral measurements at different altitudes over the northern polar cap region are analyzed for the two magnetic storm events in January 2005. Observations of neutral temperature at 250 km (Resolute Bay FPI), neutral density at 360 km (CHAMP) and 470 km (GRACE), as well as the Poynting flux (DMSP) are presented. All the measurements show enhancements at very high latitude poleward of 80° magnetic latitude during storms. Substantial heating is supplied to the polar cap during storms. Neutrals at all altitudes respond rapidly to the magnetospheric energy input.